Malakichthys formosus, a new species of small seabass (Acropomatiformes: Malakichthyidae) from southwestern Taiwan - Ng, Shing-Lai; Liu, Kwang-Ming; Joung, Shoou-Jeng (Zootaxa, 2023)
A new species of Malakichthys is described based on six specimens collected from deepwaters off southwestern Taiwan, northwestern Pacific Ocean. The new species, M. formosus sp. nov., exhibits distinct morphological characters, primarily characterized by the absence of chin spines, distinguishing it from other congeners with the exception of M. levis and M. mochizuki. It differs from the two species by having more lateral-line scales, a shorter distance between the snout and dorsal-fin origin, a shallower head, fewer scale rows below the lateral line, and the structure of the first anal-fin pterygiophore. Eight species are now recognized in Malakichthys.